Developmental perspective in relation to media effect / Syed Jamal Abdul Nasir Syed Mohamad - Syed Mohamad, Syed Jamal Abdul Nasir (Universiti Teknologi MARA Cawangan Pahang, 2000)
This paper is disclosing the influence of human development towards media effect. Media effect is found varies towards different stages of human beings. Human beings learn differently from media that they are exposed to. This is because human beings have their mental development in stages and thus they conceptualize different ideas at different stages.